2015
DOI: 10.1371/journal.pone.0119715
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, Identification and Functional Characterization of Bovine Free Fatty Acid Receptor-1 (FFAR1/GPR40) in Neutrophils

Abstract: Long chain fatty acids (LCFAs), which are ligands for the G-protein coupled receptor FFAR1 (GPR40), are increased in cow plasma after parturition, a period in which they are highly susceptible to infectious diseases. This study identified and analyzed the functional role of the FFAR1 receptor in bovine neutrophils, the first line of host defense against infectious agents. We cloned the putative FFAR1 receptor from bovine neutrophils and analyzed the sequence to construct a homology model. Our results revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 51 publications
4
42
0
Order By: Relevance
“…Neutrophils are the only tissue in which GPR40 was detected. Since GPR40 has already been implicated in calcium-dependent degranulation and superoxide production in bovine neutrophils [ 53 ], its presence was certainly expected. Its downregulation over time suggests lower PMNL activity postpartum.…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophils are the only tissue in which GPR40 was detected. Since GPR40 has already been implicated in calcium-dependent degranulation and superoxide production in bovine neutrophils [ 53 ], its presence was certainly expected. Its downregulation over time suggests lower PMNL activity postpartum.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of FFAR1/GPR40 in pancreatic b cells (human, mouse or rat) have demonstrated that FFAR1/GPR40 activation stimulates PLC and intracellular calcium. 42 Human FFAR1, which shows 85% identity with the bovine receptor, 10 induced PI3K, ERK1/2 and p38 MAPK activation. 19 In bovine neutrophils, natural and synthetic ligands of FFAR1/GPR40 stimulated intracellular calcium mobilization and PLC and PKC activation, 10 pathways that have been associated with MAPK activation.…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophils (1 Â 10 6 ) were incubated with 10 mM UO126, 10 mM SB203580, 10 mM LY294002 or vehicle (0.1% DMSO) for 5 min at 37 C, and then with FFAR1/GPR40 agonists (10 mM GW9508, 100 mM LA or 300 mM OLA) for 5 min at 37 C. After incubation, the neutrophils were centrifuged at 600 g for 6 min, and equal amounts of supernatants were assayed for gelatinase activity by zymography, as described. 10 Briefly, 10 ml supernatant was loaded on 10% polyacrylamide gels (0.75-mm thick) containing 0.2% gelatine. The gels were run at 200 V for 1 h in a Bio-Rad Mini Protean II apparatus (Bio-Rad Laboratories, Richmond, CA, USA) and then soaked twice in 2.5% Triton X-100 in distilled water on a shaker at room temperature for 30 min.…”
Section: Determination Of Mmp-9 Activity By Zymographymentioning
confidence: 99%
See 1 more Smart Citation
“…However, we still cannot rule out the possibility that there might be other regulatory mechanisms underlying the OA‐induced MMP upregulation seen in cultured VSMCs. Intriguingly, OA is recently found to upregulate MMP‐9 release from human neutrophils through a FFA receptor 1 (FFAR1)‐regulated mechanism [Manosalva et al, ]. Our unpublished data demonstrated that treatment with TAK‐875, an FFAR1 agonist, but not with TUG‐891, an FFAR4 agonist, significantly increased LOX‐1 expression in cultured VSMCs (Fig.…”
Section: Discussionmentioning
confidence: 57%